Impact of the practising anesthesiologist team member on the laryngeal mask cuff pressures and adverse event rate - Yurtlu,Bülent Serhan (2015)
OBJECTIVE: We have planned to evaluate the laryngeal mask cuff pressures (LMcp) inflated by anesthesia workers of several seniority, without using manometer. METHODS: 180 patients scheduled to have short duration surgery with laryngeal mask were included in the study. Five anesthesia specialists (Group S), 10 residents (Group R) and 6 technicians (Group T) inflated the LMc; thereafter LMcp were measured with pressure manometer. Participants have repeated this practice in at least five different cases. LMcp higher than 60 cm H2O at the initial placement or intraoperative period were adjusted to normal range. Sore throat was questioned postoperatively. Groups were compared in terms of mean LMcp and occupational experience. RESULTS: At the settlement of LM, LMcp pressures within the normal range were determined in 26 (14.4%) cases. Mean LMcp after LM placement in Group S, R and T were 101.2 ± 14.0, 104.3 ± 20.5 cm H2O and 105.2 ± 18.4 cm H2O respectively (p > 0.05). Mean LMcp values in all measurement time periods within the groups were above the normal limit (60 cm H2O). When groups were compared in terms of LMcp, no difference has been found among pressure values. Occupational experience was 14.2 ± 3.9; 3.3 ± 1.1 and 6.6 ± 3.8 years for specialists, residents and technicians respectively and measured pressure values were not different in regard of occupational experience. Seven (3.9%) patients had sore throat at the 24th hour interview. CONCLUSION: Considering lower possibility of normal adjustment of LMcp and ineffectiveness of occupational experience to obtain normal pressure values, it is suitable that all anesthesia practitioners should adjust LMcp with manometer.